Considerations on the role of institutions and networks in the bioeconomy: Three case studies from Ghana and Brazil - Lilli Scheiterle; Regina Birner (University of Bonn, Center for Development Research (ZEF), 2020)
An increasing number of governments around the world have developed a bioeconomy strategy. These strategies have important implications for the agricultural sector, technological innovation as well as sustainability and food security. The cross-cutting nature of the bioeconomy demands synergies and links between value chains to create innovations for optimal use of biomass for industrial purposes without creating competition for food products. Institutional networks are pivotal for the sustainable production and use of biological resources, as well as for the development of innovative processes to exploit the potential of biomass. This working paper uses three cases studies to explore aspects that need to be addressed to take advantage of the considerable untapped potential of the bioeconomy. The first case study highlights determinants of persisting low maize yields in northern Ghana, despite the introduction of a fertilizer subsidy program. Input subsidy policies are largely regarded as an instrument to increase crop productivity and contribute to food security. The second case study explores the role of female-led market institutions in Ghana. Markets are central to the development of the bioeconomy and as such, trader organizations have a key role to play in the value chain. The third case study investigates how well Brazil, the world leader in sugarcane production, is positioned to realize the shift from a fossil-based to a bio-based economy (bioeconomy). Subsequently, the role institutions and networks play in the development of the bioeconomy in two countries at different points of the value chain are discussed. We conclude that strengthening efforts to tailor site-specific solutions that consider the interdisciplinary nature of crop production, marketing, and development of processes is crucial to the bioeconomy. Overall, more attention to innovation networks is required to master the challenges of the bioeconomy and take full advantage of its opportunities.
Keywords: 330; Biomass-based value web; governance; maize productivity; collective action; coordination